The removal of the parliamentary immunity. Is it the best decision? - López Aburto, Yerina Rocio (2020)
As a part of the political reform promoted by the government of Matín Vizcarra, it was proposed the reform of Parliamentary Immunity, because it is an institutional prerogative criticized. Attending to the popular pressure, in july 2020 the Parliament approved in the first vote the removal of parliamentary immunity of the members of the parliament and other officials. To make effective the removal of parliamentary immunity it requires a second vote, that will take place in 2021. In that way, the purpose of this article is to analyze if the removal of this constitutional guarantee is the best decision for our constitutional democracy.